Friction and wear studies on brake lining using ansy (FEA ) / Abdul Razak Ismail and Zainuddin Timin - Ismail, Abdul Razak; Timin, Zainuddin (Faculty of Mechanical Engineering, 1995)
Several types of lining materials are already in use for brake application. Different materials have different friction and wear characteristics. These types of lining materials are used for different applications, depending on their characteristics. . In this project, studies are made on the friction and wear of brake lining materials for disc brakes using ANSYS FEA (Finite Element Analysis) software available at CADEM centre as a tool. Asbestos, sintered and polyimide materials are selected for these case studies. Using FEA the distribution of force acting on each element is found out. Using this data, the friction and wear of the above materials are calculated and the material having higher friction is reported.